Economic Crimes under the Law of Republic of Serbia - Miletić, Vladimir (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
The author analyzes concepts, characteristics, elements, forms of manifestation and system of economic crimes as a particular form of public offences in criminal law of the Republic of Serbia from the scope of judicial theory and court practice. Economic crimes are extremely dangerous social forms of illegal misconduct by authorized persons, legal entities and entrepreneurs. In the field of economic and financial businesses in general, but particularly in trade, manufacturing, the system of payment, the financial or fiscal system, insurance, etc., derogation of regulations causes damage and loss to other legal entities’ property or the community as a whole. Economic crimes are the most difficult form of economic delinquency, including commercial criminal offences and economic offences for which perpetrators have been fined, received suspended sentences, and had protective measures imposed.